Multi‐Scale Geomagnetic Forcing Derived From High‐Resolution Observations and Their Impacts on the Upper Atmosphere. Issue 12 (27th December 2022) - Sheng, Cheng; Deng, Yue; Bristow, William A.; Nishimura, Yukitoshi; Heelis, Roderick A.; Gabrielse, Christine
Abstract: Techniques developed in the past few years enable the derivation of high‐resolution regional ion convection and particle precipitation patterns from the Super Dual Auroral Radar Network (SuperDARN) and Time History of Events and Macroscale Interactions during Substorms All‐Sky Imager (ASI) observations, respectively. For the first time in this study, a global ionosphere‐thermosphere model (GITM) is driven by such high‐resolution patterns to simulate the I‐T response to the multi‐scale geomagnetic forcing during a real event. Specifically, GITM simulations have been conducted for the 26 March 2014 event with different ways to specify the high‐latitude forcing, including empirical models, high‐resolution SuperDARN convection patterns, and high‐resolution ASI particle precipitation maps. Multi‐scale ion convection forcing estimated from high‐resolution SuperDARN observations is found to have a very strong meso‐scale component. Multi‐scale convection forcing increases the regional Joule heating (integrated over the high‐resolution SuperDARN observation domain) by ∼30% on average, which is mostly contributed by the meso‐scale component. Meso‐scale electron precipitation derived from ASI measurements contributes on average about 30% to the total electron energy flux, and its impact on the I‐T system is comparable to the meso‐scale convection forcing estimated from SuperDARN observations. Both meso‐scale convection and precipitation forcing are found to enhance ionospheric and thermospheric disturbances with prominent structures and magnitudes of a few tens of meters per second in the horizontal neutral winds at 270 km and a few percent in the neutral density at 400 km through comparisons between simulations driven by the original and smoothed high‐resolution forcing patterns. Plain Language Summary: Empirical models are usually used by physical models to study how the Earth's upper atmosphere responds to the mass, momentum and energy inputs from the solar wind and the magnetosphere. However, empirical models usually provide statistically averaged patterns of the solar wind and magnetospheric forcing, and meso‐ (100–500 km) and small‐scale (<100 km) forcing may not be represented in those models. In this study, we use the forcing patterns derived from high‐resolution radar and imager measurements to drive the global ionosphere‐thermosphere model, which is a non‐hydrostatic model of the Earth's upper atmosphere. Both large‐ and meso‐scale forcing are included in these observation‐based forcing patterns. Meso‐scale forcing derived from high‐resolution measurements during a substorm event has been examined and its impact on the Earth's upper atmosphere has been evaluated. Key Points: The high‐resolution Super Dual Auroral Radar Network (SuperDARN) observations display multi‐scale plasma convection Multi‐scale, primarily meso‐scale, SuperDARN convection forcing increases the regional Joule heating by ∼30% on average Meso‐scale geomagnetic forcing cause rich structures with notable magnitudes in upper atmospheric disturbances